Implementasi Manajemen Mutu Pendidikan Islam di Madrasah Aliyah Negeri I Tanjung Pandan Kabupaten Belitung - Suparta, Suparta (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2017)
Abstract: Implementation of Quality Management of Islamic Education in MAN I Tanjung Pandan has been done with the maximum. Efforts to improve the quality of education in this school began from the improvement of human resources standards both in the form of educators and learners and educational personnel. The manifestation of this improvement of human resources by implementing the quality standard of education that has been formulated based on Quality Management Principles of Education. In addition to human resources improvement is also seen in curriculum management, learning and classroom management and facilities management and infrastructure. On the basis of some specified managerials then all Teachers, Students and Educational Personnel must implement. If not perform in accordance with applicable proceduresand regulations then be subject to disciplinary strikes both on the Educator and the Learners. Abstrak: Implementasi Manajemen Mutu Pendidikan Islam di MAN I Tanjung Pandan sudah dilakukan dengan maksimal. Usaha untuk meningkatkan mutu pendidikan di Sekolah ini di mulai dari peningkatan standar sumber daya Manusia baik berupa pendidik maupun peserta didik dan tenaga kependidikan. Wujud dari peningkatan SDM ini dengan cara melaksanakan standar mutu pendidikan yang telah disusun berdasarkan Prinsip-prinsip Manajemen Mutu Pendidikan. Selain berupa SDM peningkatan juga terlihat pada manajemen Kurikulum, Manajemen pembelajaran dan kelas serta manajemen sarana dan prasarana. Atas dasar beberapa manajerial yang sudah ditentukan tersebut maka seluruh Guru, Siswa dan Tenaga kependidikan harus melaksanakan. Bila tidak melaksanakan sesuai dengan prosedur dan peraturan yang berlaku maka dikenakan teguran disiplin baik pada Pendidik maupun pada Peserta Didik.